Observations on the biology of Afrotropical Hesperiidae (Lepidoptera) principally from Kenya. Part 3. Pyrginae: Celaenorrhinini - Cock, Matthew J. W.; Congdon, T. Colin E. (Zootaxa, 2011)
Partial life histories for 15 species and two subspecies of Afrotropical Celaenorrhinini (Hesperiidae: Pyrginae) are described and illustrated: Celaenorrhinus plagiatus Berger, C. undescribed nr. dargei Berger, C. proxima proxima (Mabille), C. proxima maesseni Berger, C. zanqua Evans, C. humbloti (Mabille), C. sanjeensis Kielland, C. galenus opalinus Butler, C. galenus biseriata Butler, C. handmani Collins & Congdon, Eretis umbra maculifera Mabille & Boullet, E. lugens (Rogenhofer), Sarangesa phidyle (Walker), S. motozi (Wallengren), S. haplopa Swinhoe, S. maculata (Mabille) and Triskelionia compacta (Evans). The published information on other species of the tribe is summarised, and generalisations are made for the tribe in Africa. All species of Celaenorrhinus, Eretis and Sarangesa spp. reared to date use Acanthaceae as food plants, but T. compacta feeds on a Fabaceae and Ortholexis hollandi Druce feeds on an Apocynaceae. Three groups of Celaenorrhinus spp. are recognised based on their pupae: Group 1 having brown pupae with cephalic projections, Group 2 having green pupae, with no cephalic projections, and a very long proboscis sheath, and a third group based on published illustrations of the life history of C. mokeezi (Wallengren), in which the pupa is generally covered with white powder, and has just a short blunt frontal projection. Loxolexis Karsch is returned to synonomy with Katreus Watson, stat.rev. and Ortholexis Karsh stat rev. is reinstated for the species which had been placed in Loxolexis: O. holocausta (Mabille) comb. nov., O. dimidia (Holland) comb. nov. and O. hollandi Druce comb. rev.